Pharmacologic rescue of hyperammonemia-induced toxicity in zebrafish by inhibition of ornithine aminotransferase - Zielonka, Matthias; Breuer, Maximilian; Okun, Jürgen G.; Carl, Matthias; Hoffmann, Georg F.; Kölker, Stefan (PLOS ONE, 2018)
Hyperammonemia is the common biochemical hallmark of urea cycle disorders, activating neurotoxic pathways. If untreated, affected individuals have a high risk of irreversible brain damage and mortality. Here we show that acute hyperammonemia strongly enhances transamination-dependent formation of osmolytic glutamine and excitatory glutamate, thereby inducing neurotoxicity and death in ammoniotelic zebrafish larvae via synergistically acting overactivation of NMDA receptors and bioenergetic impairment induced by depletion of 2-oxoglutarate. Intriguingly, specific and irreversible inhibition of ornithine aminotransferase (OAT) by 5-fluoromethylornithine rescues zebrafish from lethal concentrations of ammonium acetate and corrects hyperammonemia-induced biochemical alterations. Thus, OAT inhibition is a promising and effective therapeutic approach for preventing neurotoxicity and mortality in acute hyperammonemia.